2019
DOI: 10.1080/00309230.2019.1660387
|View full text |Cite
|
Sign up to set email alerts
|

School museums as dynamic areas for widening the heuristic potential and the socio-cultural impact of the history of education. A case study from Italy

Abstract: The contribution aims at introducing some points to reflect on the new role which university museums of schools and education can play today in the wake of current international processes of revitalisation of university heritage and museums, particularly in the light of the new objectives of the University Third Mission. Starting from the experience of the "Paolo and Ornella Ricca" School Museum in Macerata University, the authors illustrate how university museums can achieve several goals: on the one hand, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The latter comprises not only teaching collections but also libraries and archives, e.g., [73][74][75], which still need to be correctly preserved and made known to students and teachers. To achieve this goal, Meda and D'Ascenzo [67,76] underlined the establishment of educational museums, mostly based on academic institutions [77], entirely devoted to preserving and displaying the school heritage such as the Museo della Scuola e dell'Educazione "Mauro Laeng" in Rome, e.g., [78], the Museo dell'Educazione in Padua, e.g., [79], the Museo della Scuola e del Libro per l'Infanzia in Turin, e.g., [80], the Museo Didattico e della Didattica in Piacenza, e.g., [81], the Museo della Scuola "Paolo e Ornella Ricca" in Macerata, e.g., [82,83], and the Museo della scuola e dell'educazione popolare in Campobasso, e.g., [84]. Furthermore, it is noteworthy the establishment of the Italian Society for the Study of the Historical-Educational Heritage (Società Italiana per lo Studio del Patrimonio Storico-Educativo, SIPSE) in 2017, aiming to recover, safeguard, and make accessible to scholars and the general public the school heritage kept in local museums, centers for documentations, and educational institutions, e.g., [85,86].…”
Section: School Heritage In Italymentioning
confidence: 99%
“…The latter comprises not only teaching collections but also libraries and archives, e.g., [73][74][75], which still need to be correctly preserved and made known to students and teachers. To achieve this goal, Meda and D'Ascenzo [67,76] underlined the establishment of educational museums, mostly based on academic institutions [77], entirely devoted to preserving and displaying the school heritage such as the Museo della Scuola e dell'Educazione "Mauro Laeng" in Rome, e.g., [78], the Museo dell'Educazione in Padua, e.g., [79], the Museo della Scuola e del Libro per l'Infanzia in Turin, e.g., [80], the Museo Didattico e della Didattica in Piacenza, e.g., [81], the Museo della Scuola "Paolo e Ornella Ricca" in Macerata, e.g., [82,83], and the Museo della scuola e dell'educazione popolare in Campobasso, e.g., [84]. Furthermore, it is noteworthy the establishment of the Italian Society for the Study of the Historical-Educational Heritage (Società Italiana per lo Studio del Patrimonio Storico-Educativo, SIPSE) in 2017, aiming to recover, safeguard, and make accessible to scholars and the general public the school heritage kept in local museums, centers for documentations, and educational institutions, e.g., [85,86].…”
Section: School Heritage In Italymentioning
confidence: 99%
“…A series of interesting studies focus on school memory, at the individual, collective and public level, identifying the links that connect it to the collective imagination, to the construction of a multifaceted narrative of the learning and teaching experience (Brunelli 2019;González Gómez and Comas Rubí 2016;Meda 2022;Meda and Sani 2022;Velázquez 2019). Other studies focus on the functions of the museum and on the development of projects of active involvement of the territory, with specific attention to the social repercussions of this cultural commitment (Ascenzi, Brunelli, and Meda 2021;Brunelli and Targhetta 2022;Depaepe and Simon 2014;Myers and Grovesnor 2014). More generally, the studies that connect history to the heritage of the territory should be reported, highlighting its educational values (Ascenzi, Covato, and Zago 2021).…”
Section: The Path Of Public Sharing Of the Manifesto And Recent Trend...mentioning
confidence: 99%
“…Among the essential well-developed themes of the area, albeit without many publications, can be found "science-education", which is usually related to the learning processes, exhibitions and heritage of science museums [87,88]. "Education" is the great subject of the area of knowledge, since there is a lot of bibliography referring to educational actions [89] and digital development in museums and exhibitions [90] and the revitalisation of heritage education [91] among other topics, in which aspects related to "art" are also included, as there is a large number of articles on art museums and exhibitions [92,93], art, heritage and tourism [94], as well as education and the development of artistic sensitivity and expression [95].…”
Section: Descriptive Analysismentioning
confidence: 99%